2012
DOI: 10.7202/1008536ar
|View full text |Cite
|
Sign up to set email alerts
|

Impact de la réutilisation des eaux usées épurées en irrigation : analyse ionique des lixiviats

Abstract: Au Maroc, pays du pourtour méditerranéen, les ressources en eau sont limitées et inégalement réparties dans l’espace et dans le temps. Agadir, ville du sud du Maroc, fait partie de la région du Souss connue pour ses activités d’agriculture et de pêche. La région est connue par un climat semi-aride et un grand déficit hydrique. Afin de préserver la qualité des masses d’eau et pour diminuer les prélèvements dans le milieu naturel, il convient de chercher des approvisionnemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Moreover, effluents from M'zar plant reflect an intense particulate pollution, especially during the summer, which is explained by a large hydraulic discharge following because of a huge industrial and domestic activity in the region. The industrial effluents are mainly generated by the food processing factories in the region (fish markets, canned meats and vegetables (Mouhanni, Hamdi, Bendou, Cavalli, & Benzine, 2012;Mouhanni, Bendou, & Er-Raki, 2011). The effluents from fish processing plants are loaded with large concentration of biodegradable organic matter, salts and also suspended solids.…”
Section: Physical Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, effluents from M'zar plant reflect an intense particulate pollution, especially during the summer, which is explained by a large hydraulic discharge following because of a huge industrial and domestic activity in the region. The industrial effluents are mainly generated by the food processing factories in the region (fish markets, canned meats and vegetables (Mouhanni, Hamdi, Bendou, Cavalli, & Benzine, 2012;Mouhanni, Bendou, & Er-Raki, 2011). The effluents from fish processing plants are loaded with large concentration of biodegradable organic matter, salts and also suspended solids.…”
Section: Physical Parametersmentioning
confidence: 99%
“…This negative effect on the environment together with the human and animal populations imposes the purification. This latter is crucial in order to avoid the water shortage, to ensure the effluent physico-chemical and bacteriological quality and to make them compatible with the WHO guidelines for reuse in agriculture (Mouhanni, Hamdi, Bendou, Cavalli, & Benzine, 2012;Mouhanni, Bendou, & Er-Raki, 2011;Bali, Gueddari, & Bouchtina, 2010;Chang & Ma, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the leaching of the salts deep causes an increase in the EC in the second level 30-60 cm compared to the control. Similarly, in the same vein, studies carried out on the reuse of wastewater in different regions have reported an increase in the conductivity of plots irrigated by wastewater compared to the initial soil values [MOUHANNI et al 2012;RECHACHI 2017]. During the winter period, the EC values are reduced and this may be linked to the salts leaching from rainwater.…”
Section: Monitoring Of Soil Salinitymentioning
confidence: 89%
“…This capacity could satisfy the needs for irrigation water for the entire Agadir area (Morocco). Despite that success, studies showed an increase in salinity and leaching to the groundwater [26]. These projects came a long way from the beginnings of treated wastewater reuse.…”
Section: Reuse In Agriculturementioning
confidence: 99%